Journal of experimental orthopaedics (Springer, 2014)
The Journal of Experimental Orthopaedics is an international journal that aims to bridge the gap between orthopaedic basic science and the clinics and publishes papers related to the entire field of experimental orthopaedics, including physiological, pathological and therapeutic aspects of cartilage, bone, tendons and ligaments and other musculoskeletal tissues. It is the official basic science journal of ESSKA, the European Society of Sports Traumatology, Knee Surgery and Arthroscopy. The journal ensures rapid peer-review and publication of high quality papers.